Petra SLEEMAN & Harry PERRIDON (Eds.). The Noun Phrase in Romance and Germanic. Structure, variation and change. Amsterdão: John Benjamins. 2011. 282 pp. ISBN 978 90 272 5554 9 - Brito, Ana Maria (2017)
.